2001
DOI: 10.1034/j.1600-0870.2001.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in average and extreme precipitation in two regional climate model experiments

Abstract: Two regional climate model experiments for northern and central Europe are studied focussing on greenhouse gas-induced changes in heavy precipitation. The average yearly maximum oneday precipitation P max shows a general increase in the whole model domain in both experiments, although the mean precipitation P mean decreases in the southern part of the area, especially in one of the experiments. The average yearly maximum six-hour precipitation increases even more than the one-day P max , suggesting a decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…The effect of spatial pooling also depends on geography and the season of interest. Our result is in accordance with Räisänen and Joelsson (2001) who observed that the internal climate variability of the 1-day annual maximum precipitation is reduced stronger at larger spatial scales than the internal climate variability of the annual mean precipitation, and with Hegerl et al (2004) who, noted that changes in moderately extreme precipitation should be better detectable than changes in the annual mean precipitation because of a greater consistency between the change patterns in these extremes in climate model simulations.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The effect of spatial pooling also depends on geography and the season of interest. Our result is in accordance with Räisänen and Joelsson (2001) who observed that the internal climate variability of the 1-day annual maximum precipitation is reduced stronger at larger spatial scales than the internal climate variability of the annual mean precipitation, and with Hegerl et al (2004) who, noted that changes in moderately extreme precipitation should be better detectable than changes in the annual mean precipitation because of a greater consistency between the change patterns in these extremes in climate model simulations.…”
Section: Discussionsupporting
confidence: 94%
“…The uncertainty of the changes in extreme precipitation, has only been studied to a limited extent. Räisänen and Joelsson (2001) compared the changes in the annual mean and maximum precipitation in two 10-year control and 10-year future regional climate model simulations driven by different GCMs. They concluded that the differences between the changes in these two model experiments could be largely explained by internal climate variability as a result of the short lengths of the climate model simulations.…”
Section: Introductionmentioning
confidence: 99%
“…2004). Studies generally predict increasing frequency of heavy rainfall for Central Europe (Christensen and Christensen 2003), the UK, and Bangladesh (Palmer and Raisanen 2002), as well as increasing intensity (Raisanen and Joelsson 2001). Enhanced summer droughts are expected for southern Europe and central North America (Seneviratne et al .…”
Section: Ecological Importance Of Extreme Weather Eventsmentioning
confidence: 99%
“…These include Giorgi et al [31], Rotach et al [32], Jones et al [33], Deque et al [34], Machenauer et al [35], Raisanen et al [36], Raisanen and Joelsson [37], Rummukainen et al [38], Beniston et al [39], Christensen and Christensen [40,41], Kjellstrom [42], Semmler and Jacob [43], Sanchez et al [44], Pal et al [45], Schar et al [46]; Giorgi et al [47]; Raisanen et al [48]; Ekstrom et al [49], Deque et al [50], Gao et al [51], Diffenbaugh et al [52].…”
Section: Brief Overview Of Available Literature On European Climate Cmentioning
confidence: 99%